Death instinct and knowledge.Milano, 16 novembre 2019 BookCity - Vari, Autori (Il sogno della farfalla, 2020)
In April 2019 the first English edition of Death instinct and knowledge by Massimo Fagioli was published. This volume, for the first time translated into the scientific communication language, comprises the principles of the Human Birth theory. Last year the book was presented during three events: at the International Book Fair in Turin, in a library in Rome and during the festival BookCity in Milan. During these three occasions the presenters discussed the book’s content, particularly focusing on the importance of the translation process and the current historical context in which it was presented, after more than forty years from its first edition.